Drugs, poverty, pregnancy, and foster care in Los Angeles, California, 1989 to 1991. - Lewis, M A (1995)
To determine the characteristics and childbearing histories of women whose infants entered foster care in Los Angeles County, we examined the cases of 1,155 drug-using women whose infants were removed from them at birth and 236 non-drug-using women whose infants were also removed at birth by court order (July 1989 through March 1991). All of the women were indigent, and less than half had graduated from high school. The drug-using women frequently had criminal records, and more than a quarter were homeless. Many comparison women had mental health problems, and some (16.7%) were teenagers under court custody. Overall, 80% of all the children born to both groups of women were under court jurisdiction. Data obtained after study infants' births on 926 drug-using women observed for 18 months revealed that 22% had borne another infant who was placed in foster care; half of these infants had a positive drug immunoassay. Of the 185 non-drug-using women with 18-month follow-ups, 7.6% had borne another child who was in foster care. The magnitude of the repeated childbearing recorded among both groups of women in this study shows that preventive programs including family planning, mental health services, and drug prevention or rehabilitation programs have not reached this population.